Fabrication and Properties of Erbium-Doped Gallo-Germanate Glass Thin Films via RF-Sputtering - Ragiń, Tomasz; Markiewicz, Jakub; Markowski, Krzysztof; Sadowska, Karo; Kochanowicz, Marcin; Miluski, Piotr; Żmojda, Jacek; Dorosz, Jan; Baranowska, Agata; Dorosz, Dominik; et al. (Photonics Letters of Poland, 2025)
This paper presents novel research on amorphous thin films doped with Er3+ ions deposited using the RF-sputtering method. The obtained layers’ surface morphology, chemical composition, and optical properties were examined. Scanning electron microscopy analysis revealed a homogeneous layer structure with thicknesses ranging from 160185 nm. Energy-dispersive spectroscopy confirmed the presence of elements such as Ge, Ba, and Ga. Optical properties were measured using photoluminescence spectroscopy, showing emission in the range of 15201550 nm, indicating potential for the integrated optics emission sources. Full Text: PDF References J. Greene, "Review Article: Tracing the recorded history of thin-film sputter deposition: From the 1800s to 2017", J. Vac. Sci. Technol. A 35, 05C204 (2017). CrossRef S. Lee, J. Kim, S. Lee, H.-J. Cha, C.-S. Son, Y.-G. Son, D. Hwang, "Variations in the Physical Properties of RF-Sputtered CdS Thin Films Observed at Substrate Temperatures Ranging from 25 °C to 500 °C", Nanomaterials 12, 1618 (2022). CrossRef S. Asgary, E. Vaghri, M. Daemi, et al., "Magnetron sputtering technique for analyzing the influence of RF sputtering power on microstructural surface morphology of aluminum thin films deposited on SiO2/Si substrates", Appl. Phys. A 127, 752 (2021). CrossRef D.K. Maurya, A. Sardarinejad, K. Alameh, "Recent Developments in R.F. Magnetron Sputtered Thin Films for pH Sensing Applications—An Overview", Coatings 4, 756 (2014). CrossRef Y. Ju, L. Ai, X. Qi, J. Li, W. Song, "Review on Hydrophobic Thin Films Prepared Using Magnetron Sputtering Deposition", Materials 16, 3764 (2023). CrossRef J. Markiewicz, M. Kochanowicz, et al., "Broadband 1.5-2.1 µm emission in gallo-germanate dual-core optical fiber co-doped with Er3+ and Yb3+/Tm3+/Ho3+", Opt. Express 31, 28850 (2023). CrossRef M. Ismail, H. Farouk, M. Salem, A. Ashery, I. Battisha, "Optical properties of Er3+ doped phosphate glasses", J. Sci. Res. Sci. 36, 2019 (2020). CrossRef A. Răduță, A. Panaitescu, et al., "Effect of Deposition Working Power on Physical Properties of RF-Sputtered CdTe Thin Films for Photovoltaic Applications", Nanomaterials 14, 535 (2024). CrossRef K. Miura, Y. Arai, K. Kano, O. Hanaizumi, "Fabrication of Erbium and Ytterbium Co-Doped Tantalum-Oxide Thin Films Using Radio-Frequency Co-Sputtering", Mater. Sci. Appl. 6, 343 (2015). CrossRef E.A. Martín-Tovar, L.G. Daza, A.J.R. López-Arreguín, A.A. Iribarren Alfonso, R. Castro-Rodriguez, "Effect of substrate rotation speed on structure and properties of Al-doped ZnO thin films prepared by rf-sputtering", Trans. Nonferrous Met. Soc. China 27, 2055 (2017). CrossRef